Analisis Regulasi Jurnalistik pada Undang-Undang Pers No. 40 Tahun 1999: Analysis of Journalism Regulations in Press Law no. 40 of 1999 - Ridwan, Ridwan; Muhammad Anshar (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This study aims to analyze the journalistic regulations stipulated in Law Number 40 of 1999 on the Press and to identify its positive impacts on journalists in Indonesia. A descriptive qualitative approach is used in this research, with primary data sourced from the text of Law Number 40 of 1999 on the Press and secondary data consisting of academic literature, journal articles, and related reports. Data collection is conducted through literature study, and data analysis involves data reduction, presentation in descriptive narratives, and drawing conclusions. The results show that Law Number 40 of 1999 on the Press serves as a significant milestone in press freedom in Indonesia. This law guarantees freedom of expression, protects journalists' rights, enhances professionalism, and promotes the development of responsible media. Moreover, the existence of the Journalistic Code of Ethics and the role of the Press Council in resolving reporting disputes provide legal protection and ensure journalistic integrity. Its positive impacts include increased freedom of expression, legal protection, improved professionalism, enhanced media credibility, and encouragement of innovation in journalism. Overall, Law Number 40 of 1999 on the Press has established a strong foundation for a free, independent, and responsible press, enabling journalists to fulfill their strategic role as a pillar of democracy.